Jahresbericht 1997. : Kunsthalle zu Kiel - Schleswig-Holsteinischer Kunstverein. - Kunsthalle zu Kiel; Schleswig-Holsteinischer Kunstverein, Kiel; Christian-Albrechts-Universität, Kiel; Ermacora, Beate; Kähler, Ingeborg; Riese, Ute; Schmidt, Hans-Werner; Thurmann, Peter; Troschke, Regina (Kiel : Kunsthalle zu Kiel der Christian-Albrechts-Universität - Schleswig-Holsteinischer Kunstverein, 1997)
Voss, Jan ; Gormley, Antony ; Schmückle, Miron ; Pechstein, Max ; Jenssen, Olav Christopher ; Kluge, Gustav ; Geismar, Jarg ; Porzner, Hans-Peter ; Rist, Pipilotti ; Goldin, Nan ; Graham, Dan ; Henderikse, Jan
Duits
boek